2013
DOI: 10.5301/ijao.5000196
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Dialysance and Determination of Kt/V in on-line Hemodiafiltration with Simultaneous Pre- and Post-dilution

Abstract: Direct calculation of Kt/V from estimating K by OCM and V by BCM is consistent with the usual indirect estimation by the second generation Daugirdas equation. Therefore, the regular determination of V by BCM allows the estimation of single-pool Kt/V at each session without the need of blood sampling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
1
0
4
Order By: Relevance
“…Theoretical considerations show that the value of ionic dialysance depends on recirculation 9,10 and predilution procedure, 12 which is confirmed by in‐vivo experiments 13‐15 . Many studies have shown a strong correlation and good agreement (mean difference less than 3%) between ionic dialysance and effective urea clearance defined as dialyzer urea clearance corrected by the deleterious effect of recirculation and possibly predilution 16‐20 .…”
Section: Ionic Dialysance Monitoringmentioning
confidence: 78%
“…Theoretical considerations show that the value of ionic dialysance depends on recirculation 9,10 and predilution procedure, 12 which is confirmed by in‐vivo experiments 13‐15 . Many studies have shown a strong correlation and good agreement (mean difference less than 3%) between ionic dialysance and effective urea clearance defined as dialyzer urea clearance corrected by the deleterious effect of recirculation and possibly predilution 16‐20 .…”
Section: Ionic Dialysance Monitoringmentioning
confidence: 78%
“…Горепосочените проучвания отчитат диапазон на аналитична грешка от ±5% до ±6%, като според Goldau et al (12) същата може да се намали при използване на краткотраен единичен динамичен импулс на проводимост, което позволява корекция за кардиопулмонална и рециркулация на достъпа, които могат значително да повлияят резултата (2,12). Други изследователи също съобщават за отлична корелация между EID и клирънса на уреята (3,16). Изследването на Lindsay et al (20) съобщават, че несъгласието между EID, измерено от Diascan, и клирънса на урея от кръвната страна се увеличава при по-високи стойности на клирънса.…”
Section: резултати и обсъжданеunclassified
“…Анализът на получените от нас резултати доказва висока корелация между валидираните показатели за диализна адекватност (spKt/V; URR) и регистрираните с онлайн мониториране чрез йонна диализа (onKt/V), като в същото време отчита сигнификантна разлика в двата метода, основаваща се предимно на използваните антропометрични формули за оценка на обема. Тази констатация е обективизирана и от други автори в предишни публикации (1,3,5,7,8,10,11,14,15,16,19,22,23). Въпреки високата сила на връзката регистрираните от нас стойности за onKt/V са с 8% по-ниски в сравнение с резултатите, използващи УКМ.…”
Section: дискусияunclassified
“…Нашите резултати демонстрират много добро съгласие на onKt/V с валидирания от препоръките на KDOQI (20) (4,5,16,18,22,23). Нашето проучване потвърди констатациите на други автори, че ОСМ има способността да подценява получената диализна доза -резултатите за onKt/V са с 8% по-ниски в сравнение със spKt/V.…”
Section: дискусияunclassified